2020
DOI: 10.1075/lllt.53.03paw
|View full text |Cite
|
Sign up to set email alerts
|

The effect of proficiency, gender, and learning style on the occurrence of negotiated interaction in communicative task performance

Abstract: Apart from positive evidence, or information about what is possible in the target language (TL), second language learners also need negative evidence, or information about what is not possible in the TL, and opportunities to engage in output production (Gass, 2003)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Ross-Feldman (2007) found that in a picture story task, either female-female or male-female dyads engaged in more language related episodes and resolved them better than male-male dyads. Pawlak (2020) found a mediating role of gender in the occurrence and outcome of CF in communicative tasks. Same gender arrangements produced the majority of instances of negotiated interaction (90%) and output modification (75%).…”
Section: Oral Corrective Feedback and Extraversion English Learning Motivation And Gendermentioning
confidence: 87%
“…Ross-Feldman (2007) found that in a picture story task, either female-female or male-female dyads engaged in more language related episodes and resolved them better than male-male dyads. Pawlak (2020) found a mediating role of gender in the occurrence and outcome of CF in communicative tasks. Same gender arrangements produced the majority of instances of negotiated interaction (90%) and output modification (75%).…”
Section: Oral Corrective Feedback and Extraversion English Learning Motivation And Gendermentioning
confidence: 87%